THE EFFECT OF WORK MOTIVATION, LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE YAYASAN PRADATA ANUGERAH NEGERI PEKANBARU - Wahyuni, R. Wiwin; Nurmansyah, Nurmansyah; Aznuriyandi, Aznuriyandi (Komunitas Manajemen Kompetitif, 2023)
The objective of this research is to assess the collectiv e influence of work motivation, leadership, and organizational culture employees performance at the Pekanbaru Pradata Anugerah Negeri Foundation.” “In writing this thesis, the writer uses data analysis with quantitative descriptive method, with data processing using SPSS”. From the results of the descriptive analysis of work motivation variables, there are 5 research indicators including physiological needs, security needs, socialization needs and affiliation with others, appreciation needs and actualization needs”. “The indicator that received the highest score is owned by thel indicator of physiological needs while the indicator with the lowest score is obtained by the indicator of self-actualization needs”. “The average score for the work motivation variable is 4,11 in the good category”. “The leadership variable has 5 research indicators including having a clear strategy, caring for subordinates and the environment, stimulating employees, maintaining cohesiveness, respecting differences and beliefs”. “The indicator with the highest score is owned by the indicator of stimulating employees while the indicator with the lowest score is obtained by the indicator of respecting differences and beliefs”. “The average score for the leadership variable is 3,72 in the good category”. “Organizational culture variables with 4 research indicators namely norms, dominant values, rules, organizational climate”. “The indicator with the highest score is obtained by the organizational climate indicator, while the indicat or with the lowest score is owned by the d ominant value”. “The average score for the organizational culture variable is 3,99 in the good category”.”Performance v ariables, with 5 research indicators including quality, productivity, knowledge, trust, availability”. “The indicator with the highest score is obtained by the quality of work while the lowest score is obtained by the knowledge indicator and the average score for the performance variable is 4,30 in the good category”. “And based on the research results, the R Square coefficient is 0,701 or 70,1%. Based on this assessment, the influence of work motivation, leadership, and organizational culture variables on employee performance is 0,701 (701%)”.